Metafizyka „Ja”. Jutryzm „Ja” Jurija Mamlejewa (doktryna filozoficzna i jej „refleksy” w powieści Włóczykije) - Pietrzycka-Bohosiewicz, Krystyna (Przegląd Rusycystyczny, 2013)
Krystyna Pietrzycka-Bohosiewicz Uniwersytet Jagielloński, Kraków, Poland PRZ.RUS@op.pl МЕТАФИЗИКА «Я». УТРИЗМ «Я» ЮРИЯ МАМЛЕЕВА (ФИЛОСОФСКАЯ ДОКТРИНА И ЕЕ «ОТБЛЕСКИ» В РОМАНЕ ШАТУНЫ) Резюме Настоящая статья посвящена краткой характеристике философской доктрины Ме-тафизика «Я» (Утризм «Я») Юрия Мамлеева, современного, мистического философа и, заодно — чрезвычайно эксцентрического и скандального писателя. Трактат был написан Мамлеевым в 60-е годы ХХ века. Одновременно с Метафизикой… он работал над своим первым большим романом — Шатуны, который, как до сих пор утверждает Мамлеев, был якобы экземплификацией его философской мысли. Именно этот роман подвергается вo второй части статьи анализу и интерпретации, прежде всего — с точки зрения главной его эстетической категории — «отвращения». THE I-METHAPHySICS. THE I-UTRISM BY YURI MAMLEEV (A PHILOSOPHICAL DOCTRINE AND ITS ‘REFLECTIONS’ IN THE NOVEL SHATUNY) Summary This paper is a short description of a philosophical doctrine called The I-Methaphysics (The I-utrism). The author of this doctrine — Yuri Mamleev — is a contemporary mistical philospher and an eccentric, scandalous writer at the same time. Mamleev wrote his treatise in 1960s. Simulteanously with The I-Methaphysics he was working at his first big novel — Shatuny, which should have exemplify his philosophical views. In the second part of this paper consists an attempt to analyse and interpret this novel, mainly according to Mamleev’s central aesthetic category — ‘abjection’.